PENGARUH KOMPENSASI DAN EMPLOYEE ENGAGEMENT TERHADAP KINERJA KARYAWAN TOKO RETAIL - Tiurmaida Margaretta Sanggam Sirait; Hesty Prima Rini (Universitas Sarjanawiyata Tamansiswa, 2025)
There is a decline in store employee performance which is an important concern for the company in maintaining store operational productivity. This study aims to analyze the effect of compensation and store employee engagement on employee performance. This study uses a quantitative approach with a saturated sampling technique, where all store employees are used as a sample with a total of 46 store employees. Data were obtained through questionnaires and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results show that compensation has a positive and significant effect on store employee performance and employee engagement has a positive and significant effect on employee performance